Solanumnigrum L. as a Hepatoprotective Agent - Rizky, Muthiana; Sastramihardja, Herri S.; Nur, Ismet Muchtar (Althea Medical Journal, 2015)
Â Â Background: Liver damage may be caused by various factors. SolanumnigrumL.fruit is known to contain flavonoid antioxidant which is responsible for its hepatoprotective effect. A study was conducted to determine the protective effect of Solanumnigrum L. fruit infusion (SNFI) on CCl4-induced hepatic cell damage in rats.Â Methods: A complete randomized experimental study was conducted on 25 male Wistar strain-white rats (Rattusnorvegicus) which were divided into five groups during the period of Septemberâ October 2012. Group I (negative control) was given standardized food and water; group II (positive control) was induced by carbon tetrachloride (CCl4) 10% paraffin intraperitoneally by 8 mL/kg body weight on the 8th day of the study; group III, IV, V (treated) were given Solanumnigrum L. fruit infusion (SNFI) by 22.5g/100mL, 45 g/100mL and 90g/100mL concentrations for 8 days, respectively, prior to CCl4 induction. The calculation of necrotic liver cells was performed in 48 hours after induction. Data were statistically analyzed using Kruskal-Wallis test followed by Mann-Whitney post-hoc test.Â Results: The percentage of necrosis liver cells in group III, IV, and V was smaller compared toÂ the positive control group. The protective effect of SNFI against CCl4-induced hepatotoxicity may be related to its ability to elevate the antioxidant agent in the body. There were significant differences in necrotic between Group II and group III, IV, V which were treated with SNFI.Â Conclusion: Further investigation is required to characterize the active ingredients and the mechanism of SNF action to confirm the hepatoprotective and antioxidant effects.Keywords: CCl4, hepatoprotective, Solanumnigrum L.DOI: 10.15850/amj.v2n1.433Â Â